E-nutrition today - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The conference on Information Technology Advances in Nutrition in Africa ITANA 2002 held in Nairobi, Kenya from 21 25 July 2002 was not at all the tame, technical gathering that some had expected. Instead, it was an enriching meeting of more...